Correction: Theoretical study and design of multifunctional phosphorescent platinum(ii) complexes containing triarylboron moieties for efficient OLED emitters. Issue 6 (9th January 2015) - Wu, Yong; Shan, Guo-Gang; Li, Hai-Bin; Wu, Shui-Xing; Ren, Xin-Yao; Geng, Yun; Su, Zhong-Min
Abstract : Correction for 'Theoretical study and design of multifunctional phosphorescent platinum(ii ) complexes containing triarylboron moieties for efficient OLED emitters' by Yong Wu et al., Phys. Chem. Chem. Phys., 2015, DOI: ; Web:10.1039/c4cp04919e .